Conference on Access to Knowledge and Information in the Social Sciences and Humanities, New York, 1972 - Fonseca, Edson Nery da (Revista de Biblioteconomia de Brasília, 1975)
CONFERENCE ON ACCESS TO KNOWLEDGE AND INFORMATION IN THE SOCIAL SCIENCES AND HUMANITIES, New York, 1972. Acces to the literature of the social Sciences and humanities. New York: Queens College Press, 1974. 199 p.